2005
DOI: 10.1152/japplphysiol.00811.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diminished overload-induced hypertrophy in aged fast-twitch skeletal muscle is associated with AMPK hyperphosphorylation

Abstract: Skeletal muscle mass declines with age, as does the potential for overload-induced fast-twitch skeletal muscle hypertrophy. Because 5'-AMP-activated protein kinase (AMPK) activity is thought to inhibit skeletal muscle protein synthesis and may therefore modulate muscle mass and hypertrophy, the purpose of this investigation was to examine AMPK phosphorylation status (a marker of AMPK activity) and its potential association with the attenuated overload-induced hypertrophy observed in aged skeletal muscle. One-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
96
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 51 publications
18
96
1
4
Order By: Relevance
“…Thomson et al (93) also reported that AICAR treatment inhibited mTOR activation, which is induced by high-frequency electrical stimulation of rat EDL muscle. Finally Thomason and Gordon (94) found a correlation between increased phosphorylation of AMPK and reduced muscle hypertrophy in aging rats.…”
Section: Cellular Energy Status and Mtor Activitymentioning
confidence: 95%
“…Thomson et al (93) also reported that AICAR treatment inhibited mTOR activation, which is induced by high-frequency electrical stimulation of rat EDL muscle. Finally Thomason and Gordon (94) found a correlation between increased phosphorylation of AMPK and reduced muscle hypertrophy in aging rats.…”
Section: Cellular Energy Status and Mtor Activitymentioning
confidence: 95%
“…In higher organisms, the role of AMPK in the regulation of aging is not clear, with some reports demonstrating a significant reduction in AMPK signaling in muscle (399,408) while others report no change (169,379) or even increased AMPK activity (494,495). The effects of metabolic stress such as hypoxia, caloric restriction, or muscle contraction on AMPK signaling in aging are equally equivocal with some studies reporting increased activation (169,379), while others have reported a reduction (349,408).…”
Section: A Aging and Longevitymentioning
confidence: 99%
“…In particular, these studies consistently reported increased Type I myosin heavy chain (Type I MHC) content in chronically overloaded rat plantaris muscles. Previous studies have also demonstrated that a sham-operated contralateral control limb does not demonstrate hy-pertrophy or alter its protein expression following synergistic ablation (Thomson andGordon 2005, Sun et al 2006), indicating that the control limb is not favored and experiences normal loading following the surgical procedure. Furthermore, the effect of overload on hypertrophy is similar when either a unilateral or a bilateral synergistic ablation model is employed (Soltow et al 2006).…”
Section: Introductionmentioning
confidence: 99%